2023
DOI: 10.3390/nu15214599
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extracts from the Aerial Parts of Inula japonica and Potentilla chinensis Alleviate Airway Inflammation in Mice That Inhaled Particulate Matter 10 and Diesel Particulate Matter

Seang-Hwan Jung,
Kyung-Sook Chung,
Chang-Seon Na
et al.

Abstract: Air pollution causes various airway diseases. However, many commonly used treatments can have high risks of side effects or are costly. To examine the anti-inflammatory properties of Inula japonica Thunb. and Potentilla chinensis Ser., a mouse model was generated via inhalation of both particulate matter 10 and diesel particulate matter, and 30% ethanol extracts of either I. japonica (IJ) or P. chinensis (PC) and a mixture of both ethanol extracts (IP) were orally administered to BALB/c mice for 12 days. IJ, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Apigenin glucoside malonate Dittrichia viscosa [71] Apigenin 7-O-glucuronide (CID: 5319484) Synonym: Scutellarin A Inula japonica [72] Apigenin O-hexuronide Telekia speciosa [63] Apigenin dihexoside Pulicaria vulgaris [73] Apigenin Asteriscus graveolens [192] [123]…”
Section: Synonym: Salipurpinmentioning
confidence: 99%
See 1 more Smart Citation
“…Apigenin glucoside malonate Dittrichia viscosa [71] Apigenin 7-O-glucuronide (CID: 5319484) Synonym: Scutellarin A Inula japonica [72] Apigenin O-hexuronide Telekia speciosa [63] Apigenin dihexoside Pulicaria vulgaris [73] Apigenin Asteriscus graveolens [192] [123]…”
Section: Synonym: Salipurpinmentioning
confidence: 99%
“…Except for the most found caffeoylquinic acids, monoacyl-, diacyl-and triacylquinic acids (conjugates with ferulic, p-coumaric and caffeic acid) or caffeoylquinates substituted with short-chain organic acids (isobutyric, methylbutyric and others) were often identified in the extracts of the Inuleae-Inulinae, mostly using HPLC-MS techniques [54,63,76,99,124,125,131,143,161,168,172,184,215,224,[328][329][330][331][332]. Metabolomic studies, performed using the hyphenated methods, revealed the presence of conjugates of hydroxycinnamic acids with shikimic acid in D. cappa [329], D. nervosa [330] and D. viscosa [170] and conjugates of hydroxycinnamic acids with aldaric acids in B. megacephala, B. riparia [124], B. speciosissimum [161], C. divaricatum [328], C. glutinosus [76], D. viscosa [136,333], I. helenium [334], I. japonica [72], I. sarana [54], P. spinosa [205], P. vulgaris [73] and P. inuloides [184]. Caffeoyltartaric acid (caftaric acid) and 2,3dicaffeoyltartaric acid (chicoric acid) were isolated from roots of I. helenium [335].…”
Section: Hydroxycinnamatesmentioning
confidence: 99%